A prediction-based algorithm for target tracking in wireless sensor networks - Rashti, S.M.; Mollanoori, M.; Nia, M.S.; Charkari, N.M. (2009 International Conference on Ultra Modern Telecommunications & Workshops, 2009)
Target tracking and environment monitoring is one of the important applications of wireless sensor networks (WSN). A class of target tracking algorithms is prediction-based algorithms which are aiming to reduce the power consumption in WSN. In this paper we present a prediction-based target tracking algorithm in which nodes form a hierarchical structure and each node tries to build a proper prediction model to prevent transmission of predictable data. As a result the power consumption of each node reduces. This method increases the lifetime of WSN as well as its stealthiness in military environments. Simulation result shows that while this method reduces the number of transmitted packets more than 30%, its tracking accuracy is acceptable.